Diagnosis and Management of Opsoclonus-Myoclonus-Ataxia Syndrome in Children: An International Perspective. Issue 3 (8th May 2022) - Rossor, Thomas; Yeh, E. Ann; Khakoo, Yasmin; Angelini, Paola; Hemingway, Cheryl; Irani, Sarosh R.; Schleiermacher, Gudrun; Santosh, Paramala; Lotze, Tim; Dale, Russell C.; Deiva, Kumaran; Hero, Barbara; et al.
Abstract : Background and Objectives: Opsoclonus-myoclonus-ataxia syndrome (OMAS) is a rare disorder of the nervous system that classically presents with a combination of characteristic eye movement disorder and myoclonus, in addition to ataxia, irritability, and sleep disturbance. There is good evidence that OMAS is an immune-mediated condition that may be paraneoplastic in the context of neuroblastoma. This syndrome may be associated with long-term cognitive impairment, yet it remains unclear how this is influenced by disease course and treatment. Treatment is largely predicated on immune suppression, but there is limited evidence to indicate an optimal regimen. Methods: Following an international multiprofessional workshop in 2004, a body of clinicians and scientists comprising the International OMS Study group continued to meet biennially in a joint professionals and family workshop focusing on pediatric OMAS. Seventeen years after publication of the first report, a writing group was convened to provide a clinical update on the definitions and clinical presentation of OMAS, biomarkers and the role of investigations in a child presenting with OMAS, treatment and management strategies including identification and support of long-term sequelae. Results: The clinical criteria for diagnosis were reviewed, with a proposed approach to laboratory and radiologic investigation of a child presenting with possible OMAS. The evidence for an upfront vs escalating treatment regimen was reviewed, and a treatment algorithm proposed to recognize both these approaches. Importantly, recommendations on monitoring of immunotherapy response and longer-term follow-up based on an expert consensus are provided. Discussion: OMAS is a rare neurologic condition that can be associated with poor cognitive outcomes. This report proposes an approach to investigation and treatment of children presenting with OMAS, based on expert international opinion recognizing the limited data available.